The RELATIONSHIP LEVEL OF KNOWLEDGE AND PREVENTION BEHAVIOR OF GASTRITIS IN STUDENTS AT AL-ISHLAH ISLAMIC BOARDING SCHOOL, TEMBALANG - Nafisa, Salma; Bakti Pertiwi, Siti Maisyaroh; Inayati, Dian (Universitas Muhammadiyah Kalimantan Timur, 2023)
Gastritis is a disease that most people complain about, especially those of productive age, which can occur due to causative factors, namely irritation and infection of the gastric mucosa and submucosa. Based on several surveys, gastritis is caused by various factors including knowledge and behavior to prevent gastritis. This study aims to determine the relationship between knowledge level and gastritis prevention behavior in Islamic boarding school students Al-Ishlah Tembalang in 2022. This type of research is an analytic observational study with a cross-sectional approach with a total sample of 34 respondents. The results of this study indicate that there is a relationship between the level of knowledge and behavior to prevent gastritis with p-value = 0.001.